Process performance and capability study on the combination of surface enhancement tool-based processes - Low, Zheng Xiang (Nanyang Technological University, 2022)
Surface enhancement process is commonly used in the manufacturing industry to improve the material property. It induces beneficial compressive residual stresses into the material and improve its fatigue life. There are many types of surface enhancement process with different deformation mechanism, such as robotic hammer peening and deep cold rolling. Each process has its advantages and disadvantages. Currently, there is a gap of study on the performance of combination between robotic hammer peening and deep cold rolling processes. This study aims to analyse the capability of the combined surface enhancement process between robotic hammer peening and deep cold rolling and evaluated based on surface roughness, surface hardness and residual stress profile. This study of combined process aims to achieve a greater improvement in material property by leveraging the benefits of each single surface enhancement process The results showed that by combining the aforementioned surface enhancement processes were able to show a greater improvement in material property, and the sequence of the processes is important. The advantages and disadvantages of each combination of surface enhancement process are identified and evaluated.